An Analysis of Exchange Rate, J Curve and Debt Burden in Pakistan: An Analysis of Bound Testing - Hina Ali; Ramzan Sheikh; Laraib Abrar (International Journal of Experiential Learning & Case Studies, 2018)
Rate of exchange is a significant monetary variable that control balance of trade. J curve theory explains that depreciation in domestic currency wills sure that foreign goods costly for the domestic persons and domestic goods are inexpensive for the other country. In this result, imports will reduce and exports will rises. Therefore, trade balance would be improved. This theory proved that J curve have no exist in Pakistan because imports of Pakistan contains a large numbers of necessities and this imports present no movement in exchange rate. Therefore, rate of exchange and balance of trade both have negative relationship. Debt and GDP have positive related with each other because Government of Pakistan takes the debt to promote the economic growth. This study opens new perspectives for the decision makers.